Examination of Psychological Strength and Target Commitment Level of Students Faculty of Sports Sciences Province - Altungül, Oğuzhan; Söyler, Didem Yavuz; Bulut, Mesut (Tamer KUTLUCA, 2023)
The aim of our study is to examine the psychological resilience and goal commitment levels of the students studying at the Faculty of Sport Sciences of Fırat University over various variables. In our study, descriptive scanning methods were used. A total of 330 individuals, 152 women and 178 men, studying at the Faculty of Sport Sciences of Fırat University, participated in our research on a voluntary basis. “Demographic Information”, “Child and Adolescent Psychological Resilience Scale” adapted into Turkish by Arslan (2015) and “goal commitment scale” adapted into Turkish by Senel and Yıldız (2016) were used on the individuals participating in the research. SPSS package program was used for data analysis. Percentage frequencies of the given data were calculated, normal distribution tests were performed, and as a result of these controls, t test was used for those with 2 variables and analysis of variance for multiple variables. Tukey test was used to determine the differences between the groups. The significance level of the study was taken as p

The aim of our study is to examine the psychological resilience and goal commitment levels of the students studying at the Faculty of Sport Sciences of Fırat University over various variables. In our study, descriptive scanning methods were used. A total of 330 individuals, 152 women and 178 men, studying at the Faculty of Sport Sciences of Fırat University, participated in our research on a voluntary basis. “Demographic Information”, “Child and Adolescent Psychological Resilience Scale” adapted into Turkish by Arslan (2015) and “goal commitment scale” adapted into Turkish by Senel and Yıldız (2016) were used on the individuals participating in the research. SPSS package program was used for data analysis. Percentage frequencies of the given data were calculated, normal distribution tests were performed, and as a result of these controls, t test was used for those with 2 variables and analysis of variance for multiple variables. Tukey test was used to determine the differences between the groups. The significance level of the study was taken as p
Examination of Psychological Strength and Target Commitment Level of Students Faculty of Sports Sciences Province
Keywords: Development of Physical Education and Education Programs; Beden Eğitimi ve Eğitim Programlarının Geliştirilmesi